Recent advances in glycopeptide hydrogels: design, biological functions, and biomedical applications - Zhang, Jinpeng; Zou, Jianghao; Ren, Jianan (Frontiers in Bioengineering and Biotechnology, 2025)
Glycopeptide hydrogels, biomaterials constructed from polysaccharides and peptides through dynamic covalent bonding and supramolecular interactions, mimic the structure and functions of the natural extracellular matrix. Their three-dimensional network structure endows them with remarkable mechanical resilience, self-healing capacity, and stimuli-responsive behavior, enabling diverse biomedical applications in tissue regeneration, wound healing, drug delivery, and antimicrobial therapies. This review comprehensively examines design principles for engineering glycopeptide hydrogels, encompassing biomolecular selection criteria and dynamic crosslinking methodologies. We analyze their multifunctional properties including antimicrobial efficacy, immunomodulation, antioxidant activity, tissue adhesion, and angiogenic potential, while highlighting smart drug release mechanisms. Applications in regenerative medicine are critically assessed, particularly in cutaneous wound healing, bone and cartilage reconstruction, myocardial repair, and neural regeneration. Finally, we delineate future directions to advance glycopeptide hydrogels, emphasizing functional sequence expansion of bioactive motifs, high-fidelity biomechanical mimicry of natural tissues, and precise simulation of organ-specific microenvironments for next-generation precision medicine.